Pengaruh ROA, ROE, DER Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018 - 2022 - Belinda Fernanda; Herlin Munthe; Rido Bancin; Ivana Rebecca Aprilia S. Depari; Kiki Hardiansyah Siregar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to examine the effect of ROA, ROE, DER and Company Size on Company Value in Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2018 - 2022. The data used is secondary data sourced from financial reports published by the capital market on the Indonesia Stock Exchange. The research method used in this research is purposive sampling method. There are 100 data samples used as research objects in this study. The results showed that ROA and DER have an effect on Firm Value while ROE and Firm Size have no effect on Firm Value. Keywords: ROA, ROE, DER, Company Size, Company Value